PENGUNGKAPAN TATA KELOLA PERUSAHAAN, KOMPETENSI AUDITOR INTERNAL, MANAJEMEN LABA: PERAN MODERASI PENGHINDARAN PAJAK - Sari , Intan Permata; Trisnawati, Estralita; Firmansyah, Amrie (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
This study examines the effect of corporate governance disclosure and internal auditor competence on earnings management. Also, this study includes tax avoidance as a moderation variable. The data for this study is sourced from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. Sampling was conducted by purposive sampling totaling 280 observations sourced from www.idx.co.id. This study's test is panel data regression analysis with a fixed-effect model. This study indicates that corporate governance disclosure and internal auditor competence are negatively associated with earnings management. Furthermore, this study finds that tax avoidance weakens the negative association between good governance disclosure and earnings management. The moderation effect is similar to the association between internal auditor competence and earnings management. This study is expected to contribute to the accounting literature as a reference for further research, especially related to earnings management issues. This research is also expected to be useful for the Financial Services Authority as a consideration for improving regulations related to implementing corporate governance.